Responding to the Investigative Pivots of Rhetoric Research. Issue 5 (20th October 2021) - Johnson, Gavin P.; Guadrón, Melissa; Hambrick, Keira; Hashlamon, Yanar; Koneval, Addison; Teston, Christa
ABSTRACT: In this essay, we offer the "investigative pivot" as a framework for teaching rhetoric researchers how to orient and withstand being re-/dis-/oriented by the research process. Investigative pivoting indexes how a researcher responds to material conditions under which they collect and analyze data. To illustrate investigative pivots, we present and analyze pivot narratives from four graduate student researchers. Drawing on the analytic power of E. Cram's rhetoric of orientation, these pivot narratives detail how we negotiate infrastructural, ideological, and institutional influences on our research process. When adopted, the investigative pivot prompts researchers to anticipate, recognize, and respond to the material-discursive hurdles of life and learning that follow us into our research sites. Such a framework, we argue, facilitates simultaneous methodological and pedagogical opportunities for students, teachers, and researchers of rhetoric.